PENGARUH MOTIVASI, REMUNERASI DAN KEPEMIMPINAN TERHADAP KINERJA PERSONIL PADA SAT SABHARA POLRES OKU TIMUR - Dyah Ayu Putriani (Jurnal Manajemen, 2021)
The population in this study amounted to 50 personnel. Based on the results of data analysis using multiple linear regression values obtained for Motivation (X1) with Personnel Performance (Y) tcount > ttable is 2.860> 2.01290 and a significant level of 0.006 < 0.05 means there is an influence between Motivation (X1) and Performance Personnel (Y). For Remuneration (X2) with Personnel Performance (Y) tcount > ttable is 5.403 > 2.01290 and a significant level of 0.000 < 0.05 means there is an influence between Remuneration (X2) and Personnel Performance (Y). As for Leadership (X3) with Personnel Performance (Y) tcount > ttable is 2.147 > 2.01290 and a significant level of 0.037 < 0.05 means there is an influence between Leadership and Personnel Performance. While simultaneous testing (together) Motivation (X1), Remuneration (X2) and Leadership (X3) affect the Performance of Personnel (Y) with a value of Fcount > Ftable that is 50.546 > 2.81. Then the coefficient of determination (Adjusted R Square) of 0.752 shows that the influence of the variables Motivation (X1), Remuneration (X2) and Leadership (X3) on Personnel Performance (Y) at the OKU East Police Sabhara Unit is 75.2% while the rest is influenced by other variables not included in this study.